Status of Adopted Child Turned into Mahram According to Syafi'i Fiqih - Muhammad Al-Furqaan; Muhammad Al Mustafa (Al Mashaadir : Jurnal Ilmu Syariah, 2022)
Adopted children who have grown up will have certain genitalia boundaries with adoptive parents. This causes the role of adoptive parents to not be realized optimally and the rights of adopted children cannot be fully fulfilled. Conversely, when adoptive parents do not pay attention to Islamic values in the practice of adopting children, this is also strictly prohibited in religion, and is considered very fatal, because it is included in the practice of tabanni during the Jahiliyya era. This research was conducted to answer problems that are currently occurring in the practice of adoption, in the form of what is the status of adopted children in Islam, how is the process for adopted children being made mahram status according to Syafi'i fiqh, and what is the law that applies to adopted children. This research is included in the category of library research. The author uses a normative approach that is descriptive in nature. The results of the research are presented by the author in the form of solving problems that occur between adoptive parents and adopted children by changing the status of adopted children to become mahrams, namely: by breastfeeding when they are child, adopting children from husband or wife relatives, and marrying adopted children. Furthermore, when the status of an adopted child has been changed to that of a mahram, then what has legal consequences is only the boundaries (aurat) of the adopted child. Meanwhile, in matters of inheritance, marriage guardianship, and lineage, nothing changes even though the adopted child has the status of a mahram. However, considering that their relationship is familiar and since childhood the adopted child has been with the adoptive parent, feeling that something is missing if the adopted child's rights are differentiated from those of his biological child, then the solution that can be made for inheritance is a mandatory will or inheritance testament so that the adopted child can still feel the inheritance those left behind and taukil marriage guardians to adoptive parents for matters of marriage guardians so that they can feel the guardianship of their adoptive parents. As for the issue of lineage, this cannot be contested in any way, because pure lineage was given by biological parents which cannot be changed even by tabanni.